Relationship Between Parental Feeding Style And Picky Eating Behavior Towards Stunting Incidents In The Work Area Of The Sungai Penuh City Health Office - Mimi Rosiska; Yosep Andri Putra; Rima Sintia (Jurnal Keperawatan Universitas Jambi, 2025)
According to the Ministry of Health's Indonesian Nutrition Status Survey (SSGI), the prevalence of stunted toddlers in East Nusa Tenggara (NTT) Province is again in the top position with a stunted toddler rate of 35.3%. This research aims to determine the relationship between parental feeding style and picky eating behavior on the incidence of stunting. This type of research is quantitative and analytical with a cross-sectional study approach. The sampling technique used in this research was the Total Sampling technique. The population in this study was all 31 stunting cases with a sample of 31 people. The location of this research was carried out in the Sungai Penuh City Health Service Work Area and was carried out in January-July 2024. The results showed that more than half of 22 (71.0%) of the respondents had very short stunting, more than half of 19 (61.3%) %) respondents with a low parental feeding style with statistical test results (Chi-Square) obtained a p-value of 0.001 and more than half of the 22 (71.0%) respondents with picky eating behavior with statistical test results (Chi-Square) obtained a p-value of 0.012. The conclusion of the research shows that there is a relationship between parental feeding style and picky eating behavior on the incidence of stunting The researchers' suggestions from the research results can be applied in daily nursing practice, such as providing counseling about parental feeding styles and picky eating. eating behavior for patients, to prevent stunting in children.